The Experience Of Health Insurance In The Syrian Arab Republic Between 2010- 2018 (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study has aimed to analyze the experience of health insurance in the Syrian Arab Republic between 2010 and 2018 in order to know the extent of development in the health insurance sector during the study period. The study also has focused on three basic indicators: the number of health insurers from 2010 to 2018, the distribution of health insurers in the government and private sector to health insurance expenses management companies, health insurance premiums. The researcher has studied and analyzed the basic health insurance indicators and showed their impact on the health development process in Syria. The study has achieved a set of  results,  the most important of which are: the poor level of insurance culture among the Syrian citizen, the impact of the war in Syria on the health insurance sector from the increase in the cost of providing health service to the insured for different types of service providers. هدفت الدراسة إلى تحليل تجربة الـتأمين الصحي في الجمهورية العربية السورية ما بين عامي 2010- 2018 بغية معرفة مدى التطور الحاصل في قطاع الـتأمين الصحي خلال فترة الدراسة. كما ركزت الدراسة على ثلاث مؤشرات أساسية وهي: عدد المؤمنين صحياً من عام 2010 وحتى 2018 , توزع المؤمنين صحياً في القطاع الحكومي والخاص على شركات إدارة نفقات الـتأمين الصحي , أقساط الـتأمين الصحي. قام الباحث بدراسة وتحليل مؤشرات الـتأمين الصحي الأساسية وإظهار مدى تأثيرها وانعكاسها على عملية التنمية الصحية في سورية. كما توصلت الدراسة إلى مجموعة من النتائج أهمها: ضعف مستوى الثقافة الـتأمينية لدى المواطن السوري, تأثير الحرب في سورية على قطاع الـتأمين الصحي من زيادة في تكلفة تقديم الخدمة الصحية للمؤمن لهم على اختلاف أنواع مزودي الخدمة.